2021
DOI: 10.3389/feart.2021.735340
|View full text |Cite
|
Sign up to set email alerts
|

Crustal Structure of the Seismogenic Volume of the 2010–2014 Pollino (Italy) Seismic Sequence From 3D P- and S-Wave Tomographic Images

Abstract: A tomographic analysis of Mt. Pollino area (Italy) has been performed using earthquakes recorded in the area during an intense seismic sequence that occurred between 2010 and 2014. 870 local earthquakes with magnitude ranging from 1.8 to 5.0 were selected considering the number of recording stations, the signal quality, and the hypocenter distribution. P- and S-wave arrival times were manually picked and used to compute 3D velocity models through tomographic seismic inversion. The resulting 3D distributions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
3
7
0
Order By: Relevance
“…In fault networks like those ruptured by the AVN, Napolitano et al (2020) found that high-scattering and highabsorption patterns obtained by increasing frequencies map the migration of the historical seismic events from the 16th century until the Pollino seismic sequence. This work supported the view that lateral fluid diffusion drove the sequence (De Matteis et al, 2021;Napolitano et al, 2021). Focal mechanism tomography highlighted the excess of pore pressure in the hypocentral area, which affected the seismicity distribution during the seismic sequence (De Matteis et al, 2021).…”
Section: Introductionsupporting
confidence: 75%
“…In fault networks like those ruptured by the AVN, Napolitano et al (2020) found that high-scattering and highabsorption patterns obtained by increasing frequencies map the migration of the historical seismic events from the 16th century until the Pollino seismic sequence. This work supported the view that lateral fluid diffusion drove the sequence (De Matteis et al, 2021;Napolitano et al, 2021). Focal mechanism tomography highlighted the excess of pore pressure in the hypocentral area, which affected the seismicity distribution during the seismic sequence (De Matteis et al, 2021).…”
Section: Introductionsupporting
confidence: 75%
“…The V P /V S ratio maps (Figures 3, 4; Supplementary Figure S7) have been obtained by dividing the value of V P by V S at each node of the inversion grid. We centered the color map to the average V P /V S value (1.78) computed by De Novellis et al (2021) and set the lower and the upper limit of the color scale at 1.5 and 2.1, respectively. This allows us to visually identify relatively high and low V P /V S anomalies if compared with the average value.…”
Section: Resultsmentioning
confidence: 99%
“…The 1,500 events selected from the starting dataset have been located using the Non-LinLoc software (Lomax et al, 2000), considering the new minimum 1D P-wave model (Supplementary Figure S1) and the V P /V S ratio of 1.78 provided by De Novellis et al (2021). We excluded all the events having less than 6 direct wave arrival times, azimuthal gap higher than 220 °and horizontal and vertical location error larger than 1 km.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations